Scaling climate services to enable effective adaptation action - Hansen, James; Furlow, John; Goddard, Lisa; Nissan, Hannah; Vaughan, Catherine; Rose, Alison; Fiondella, Francesco; Braun, Mélody; Steynor, Anna; Jack, Christoper; Chinowsky, Paul; Thomson, Madeleine C.; et al. (Global Commission on Adaptation, 2019)
Adaptation to anthropogenic climate change is the biggest challenge that humankind faces. The Intergovernmental Panel on Climate Change (IPCC) provides a synthesis of the state of the science, impacts, and policy, with a focus on long-term climate trends. However, the worst impacts of climate change are likely to come from its exacerbation of weather and climate variability. For example, higher temperatures in a particular region could lead to harsher droughts and more deadly heat waves. These are also the kinds of hazards that are regularly monitored and forecast by governments and institutions at the national, regional, and international scale.